A Theory of Interfirm Organization - Phillips, Almarin (Quarterly Journal of Economics, 1960)
I. Introduction, 602. — II. Interfirm organizations, 604. — III. Market structure, market performance, and interfirm oragnization, 610. — IV. Concluding observations on profit-maximization and traditional supply and demand analysis, 612.